Effects of matte coating on the paper surface and print density - AYDEMİR, CEM; ARMAN KANDIRMAZ, EMİNE; ÖZOMAY, ZAFER (WALTER DE GRUYTER GMBH, 2013)
In this work, standard laboratory printing applications with IGT (ISO 12647-2) were applied on uncoated and matte-coated papers using offset inks (DIN ISO 2846-1). Surface roughnesses of uncoated and coated sheets were recorded to be 195 and 13 ml/min, respectively. Air permanence values of uncoated and coated papers were found to be 5.6 and 0.103 mu m/Pa.s, respectively. Changes in the print densities were recorded up to 48 h. Print density changes for uncoated and matte-coated papers were surprisingly found to be in similar paths (8% in the first 4 h), although significant differences between surface roughnesses were recorded. Furthermore, paper samples showed similar behaviors for the percent volume changes, where drop volume disappeared within 6 min. It is concluded that matte coating did not have any significant effects on print density change and drop volume change.
Keywords: IGT printability; paper coating; paper roughness; print density; ALKYL KETENE DIMER; LIQUID PENETRATION; DROPLET; WATER; NETWORKS